Imiquimod in the treatment of anogenital warts - Michajłowski, Igor; Sobjanek, Michał; Michajłowski, Jerzy; Włodarkiewicz, Adam (Dermatology Review/Przegląd Dermatologiczny, 2009)
In the treatment of genital warts invasive and non-invasive methods are currently used. More and more often these methods are combined. We present the current knowledge on topical treatment of anogenital warts with imiquimod monotherapy or in combination with other methods. We focus on the treatment of immunocompetent patients, immunosuppressed patients (HIV positive) and pregnant women.